2017
DOI: 10.1371/journal.pone.0175734
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced disease resistance and drought tolerance in transgenic rice plants overexpressing protein elicitors from Magnaporthe oryzae

Abstract: Exogenous application of the protein elicitors MoHrip1 and MoHrip2, which were isolated from the pathogenic fungus Magnaporthe oryzae (M. oryzae), was previously shown to induce a hypersensitive response in tobacco and to enhance resistance to rice blast. In this work, we successfully transformed rice with the mohrip1 and mohrip2 genes separately. The MoHrip1 and MoHrip2 transgenic rice plants displayed higher resistance to rice blast and stronger tolerance to drought stress than wild-type (WT) rice and the ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…During seed propagation of the LsNAC069 silenced lines, we observed an increased resistance to moderate drought stress. Recently, NACs were shown to be involved in drought stress and pathogen resistance (Wang et al ., ), therefore we tested the potential effect of drought stress on LsNAC069 nuclear relocalization. For this experiment, we used PEG treatment of the plant cells in a similar manner as the CF treatment (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…During seed propagation of the LsNAC069 silenced lines, we observed an increased resistance to moderate drought stress. Recently, NACs were shown to be involved in drought stress and pathogen resistance (Wang et al ., ), therefore we tested the potential effect of drought stress on LsNAC069 nuclear relocalization. For this experiment, we used PEG treatment of the plant cells in a similar manner as the CF treatment (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…Defense relate proteins are also closely correlated with drought tolerance in plants. It has been reported that activation of plants defense against pathogens by expressing pathogen protein elicitors or R genes induces drought tolerance (Chini et al, 2004 ; Peng et al, 2015 ; Ma et al, 2017 ; Wang et al, 2017 ). Expression of Magnaporthe oryzae protein elicitors, Hypersensitive response-inducing protein 1 and 2 ( MoHrip1 and 2 ), can confer drought tolerance in rice together with enhanced blast resistance (Peng et al, 2015 ; Wang et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also other mite pests perform better on drought-stressed plants (Ximénez-Embún et al 2016 , 2017 ) and may become more serious pests in the future. To be ahead of this danger we should search for resistance traits that are displayed equally strong, or stronger, during drought, for reminiscent of, for example, the efforts for increasing diseases resistance together with drought tolerance in rice (Wang et al 2017 ), to protect tomato cultivation in the future.…”
Section: Discussionmentioning
confidence: 99%